Thrombocytopenia in hypertensive disorder of pregnancy: maternal and perinatal outcome - Varsha Deshmukh; Aulia Nasrin; SN Gadappa (New Indian Journal of OBGYN, 2022)
Background: Pregnancy induced hypertension (PIH) is one of the most common causes of both maternal and neonatal morbidity. A variety of haematological abnormalities may occur in women with PIH of which thrombocytopenia is the most common. Objectives: This study was done to estimate the incidence of thrombocytopenia in pregnant women diagnosed with PIH and to correlate the severity of PIH with the degree of thrombocytopenia. The maternal and perinatal outcome was analyzed according to the severity of thrombocytopenia in hypertensive disorders of pregnancy. Material and methods: This is a prospective observational study conducted in the Department of OBGY, GMCH Aurangabad during a period of 2 years (September 2017 to October 2019) in women who were admitted in labor room or ANC ward with diagnosis of hypertensive disorder of pregnancy with thrombocytopenia. Data from case files was collected, compiled, and analyzed. Results: In the present study, preeclampsia - nonsevere (20%) and severe (50%), accounted for most of the cases followed by eclampsia (13%) and gestational hypertension (17%). In the 100 cases, mild thrombocytopenia (25%), moderate thrombocytopenia (62%), severe thrombocytopenia (13%), were encountered. Poor maternal outcome was seen in 30.6% cases due to postpartum haemorrhage, DIC, abruption and two maternal deaths in severe thrombocytopenia group. The maternal outcome was significantly associated with severity of thrombocytopenia of patients (p=0.017). The severity of thrombocytopenia was significantly associated with perinatal outcome of patients (p=0.038). Out of 100 newborns, there were 16 IUFD and 13 early neonatal deaths. IUFD accounted for 38.4% in severe thrombocytopenia group and 12% in mild thrombocytopenia group (p=0.064). Conclusions: Thrombocytopenia in hypertensive disorder of pregnancy increases maternal and perinatal morbidity and mortality. Careful follow up during and after pregnancy is recommended.